Hubungan Serious Leisure dan Tingkat Kecemasan Menghadapi Masa Pensiun - Valencia Giovanni Permana; Agustina Hendriati (Jurnal Perkotaan, 2016)
Retirement bring significant changes in a person’s life. Middle-aged persons need to prepare themselves for such changes. This is especially true in the case of involuntary retirement which usually creates more anxiety. One way to prepare for retirement is through serious leisure activities. With serious leisure, self-development may be achieved and it will help the person to face the retirement. The purpose of this study was to test a negative correlation between serious leisure and the level of pre-retirement anxiety. Serious leisure was measured with Serious Leisure and Measurement Inventory (SLIM) which consists of 51 items, and the pre-retirement anxiety was measured with Retirement Anxiety Scale (RAS), which consists of 22 items. The samples were 119 people aged 50 to 53 years old, still working in the formal sector and would face retirement in a few years. Results from this study were analyzed quantitatively using Pearson's Product Moment and it was found significantly that serious leisure is negatively correlated with the level of pre-retirement anxiety. The result was discussed in regard to methodological and practical relevance.